Analisis Perilaku Conductor Leg Dari Monopod Platform Akibat Pembebanan Lateral Dan Aksial Dengan Metode Elemen Hingga - Kunthi Ulfa Diatri Prabawani; Rudi Walujo Prastianto; Handayanu Handayanu (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
A minimalist platform is a platform with a smaller and simpler deck and has less equipment. Minimalist platforms are generally designed for fields with lower reservoir reserves and are expected to have low costs in terms of fabrication and installation. One of the studies in developing a minimalist platform is about a conductor pipe that functions as a well and as the leg of the platform. This platform is susceptible to deflection under lateral and axial loads. In this research, an analysis will be carried out on the conductor pipe as a single pile which is subjected to a combination of lateral and axial loads to determine the stress and deflection that occurs in the conductor leg. This study was conducted using the finite element method with ABAQUS software. Inclination variations were carried out to determine the strength of the conductor leg when an inclination occurs. The result of this study was found that the conductor leg with an inclination of up to 1.5 degrees still had a stress below 0.6 yield. The result of this analysis shows that the conductor leg’s stress increases with increasing inclination. The maximum stress occurs at 1.5o of inclination which is 82.45 MPa under operating conditions and 125.45 MPa under extreme conditions. This stress is still below the allowable stress of 213 MPa (0.6 yields).